Transcription-Replication Collisions and Chromosome Fragility - Wu, Wei; He, Jing Na; Lan, Mengjiao; Zhang, Pumin; Chu, Wai Kit (Frontiers in Genetics, 2021)
Accurate replication of the entire genome is critical for cell division and propagation. Certain regions in the genome, such as fragile sites (common fragile sites, rare fragile sites, early replicating fragile sites), rDNA and telomeres, are intrinsically difficult to replicate, especially in the presence of replication stress caused by, for example, oncogene activation during tumor development. Therefore, these regions are particularly prone to deletions and chromosome rearrangements during tumorigenesis, rendering chromosome fragility. Although, the mechanism underlying their “difficult-to-replicate” nature and genomic instability is still not fully understood, accumulating evidence suggests transcription might be a major source of endogenous replication stress (RS) leading to chromosome fragility. Here, we provide an updated overview of how transcription affects chromosome fragility. Furthermore, we will use the well characterized common fragile sites (CFSs) as a model to discuss pathways involved in offsetting transcription-induced RS at these loci with a focus on the recently discovered atypical DNA synthesis repair pathway Mitotic DNA Synthesis (MiDAS).